An approach to estimating the potential production benefits from improved water management for rice - Small, L.E.; Chen, C.L. (1986)
Production benefits of improved allocation of irrigation water are often difficult to measure. In situations of irrigated rice cultivation, both ex post estimates of such benefits and ex ante estimates of the maximum potential benefits of further improvements in allocation of a given water supply are possible using a conceptual framework which (1) functionally relates weekly water supplies to weekly measures of average water shortage on individual paddy fields; (2) aggregates the weekly water shortage measures into a seasonal water shortage index; and (3) relates, via a production function, the seasonal water shortage index to yields. An empirical application of this framework estimates the potential increase in production from further improvements in water allocation in one Philippine irrigation system to be negligible.